2022
DOI: 10.3389/fnhum.2022.861136
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Alterations in Gait Features in Growing Children With Duchenne Muscular Dystrophy

Abstract: Prolonging ambulation is an important treatment goal in children with Duchenne muscular dystrophy (DMD). Three-dimensional gait analysis (3DGA) could provide sensitive parameters to study the efficacy of clinical trials aiming to preserve ambulation. However, quantitative descriptions of the natural history of gait features in DMD are first required. The overall goal was to provide a full delineation of the progressive gait pathology in children with DMD, covering the entire period of ambulation, by performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Based on these results, 3DGA could be considered as potential biomarker or even surrogate endpoint, in addition to functional endpoints such as 6MWT or NSAA, to enhance detection of treatment effect in clinical trials, particularly for those with more preserved muscle function. From their mixed crosssectional longitudinal study, Vandekerckhove et al 52 reported on the overall gait index GPS, which represents the difference in 16 kinematic parameters between an individual DMD subject and the control group. The increase in GPS confirmed the overall progressive gait pathology seen in children with DMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, 3DGA could be considered as potential biomarker or even surrogate endpoint, in addition to functional endpoints such as 6MWT or NSAA, to enhance detection of treatment effect in clinical trials, particularly for those with more preserved muscle function. From their mixed crosssectional longitudinal study, Vandekerckhove et al 52 reported on the overall gait index GPS, which represents the difference in 16 kinematic parameters between an individual DMD subject and the control group. The increase in GPS confirmed the overall progressive gait pathology seen in children with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Vandekerckhove et al 52 . described a mixed cross‐sectional longitudinal study in 27 DMD patients, with a cross‐sectional component (children measured only once) and a longitudinal component (children with repeated measures over time).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workflow to build the linear mixed-effects models as described by Vandekerckhove et al was applied. 22 With the jth observation in child i, for covariate c, the response for the different muscle outcomes was modelled as follows:…”
Section: Discussionmentioning
confidence: 99%
“…random intercept and random slope respectively. The workflow to build the linear mixed‐effects models as described by Vandekerckhove et al was applied 22 . With the j th observation in child i , for covariate c , the response for the different muscle outcomes was modelled as follows:Responseijgoodbreak=)(α1cgoodbreak+a1icgoodbreak+)(β1cgoodbreak+b1icgoodbreak×ageijcgoodbreak+ε)(1italicijcwhere α 1 is the intercept, a 1 i the random intercept, β 1 the regression coefficient, b 1 i the random slope, and ε (1) ij the measurement error.…”
Section: Methodsmentioning
confidence: 99%